The Centrality of Obesity in the Course of Severe COVID-19 - Liu, Danfei; Zhang, Tongyue; Wang, Yijun; Xia, Limin (Frontiers in Endocrinology, 2021)
The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global public health challenge. Most patients do not experience severe complications, but approximately 25% of patients progress to acute respiratory distress syndrome (ARDS), and the mortality rate is approximately 5–7%. Clinical findings have determined several risk factors for severe complications and mortality in COVID-19 patients, such as advanced age, smoking, obesity, and chronic diseases. Obesity is a common and serious health problem worldwide that initiates a cascade of disorders, including hypertension, cardiovascular disease (CVD), diabetes mellitus, and chronic kidney disease (CKD). The presence of these disorders is linked to a more severe course of COVID-19. Given the “epidemic” of obesity worldwide and the importance of obesity in the progression of COVID-19, we investigated the mechanisms through which obesity increases the susceptibility to and severity of COVID-19 to support the selection of more appropriate therapies for individuals with obesity.